The Process of Curriculum Innovation: Dimensions, Models, Stages, and Affecting Factors - Yuli Supriani; Fitri Meliani; Asep Supriyadi; Supiana Supiana; Qiqi Yuliati Zaqiah (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to explain the dimensions, models, stages, and affecting factors in the curriculum innovation process. Curriculum becomes very important in educational institutions because the curriculum is the "heart" of education. This research uses a descriptive qualitative approach with library research methods, using synthesis and content analysis. The results showed that the curriculum is a set of tools to achieve a goal, ranging from planning, and implementation to evaluation. Innovation or curriculum renewal needs to be done because education practitioners must adjust to the development of a society that is always changing and continues to grow. Innovations appear to answer critical issues in education. There are two models of innovation processes: the individual and the organizational models. Effecting factors in the curriculum innovation process are the vision-mission of education, population growth, the development of science-technology, and the relevant educational demands. Innovation must be the result of original and creative thinking. The application of innovation must be efficient, easy to use, and serves comfort for students, teachers, and practitioners of education.